2004
DOI: 10.1007/s00192-004-1210-4
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic organ support in pregnancy and postpartum

Abstract: The purpose of this study was to evaluate pelvic organ support during pregnancy and following delivery. This was a prospective observational study. Pelvic organ prolapse quantification (POPQ) examinations were performed during each trimester of pregnancy and in the postpartum. Statistical comparisons of POPQ stage and of the nine measurements comprising the POPQ between the different time intervals were made using Wilcoxon's signed rank and the paired t-test. Comparison of POPQ stage by mode of delivery was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 17 publications
3
51
1
Order By: Relevance
“…In our study the women were examined sitting 45°upright, whereas in the other two studies the patient was examined in supine lithotomy position and left lateral position, respectively. 14,16 Although POP-Q is validated for examining women in all three positions, these studies were performed in older, non-pregnant women. [26][27][28][29] The studies comparing dorsal lithotomy position with sitting upright found a higher degree of prolapse in the upright position, whereas we believe this to be opposite in the case of an enlarged uterus.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study the women were examined sitting 45°upright, whereas in the other two studies the patient was examined in supine lithotomy position and left lateral position, respectively. 14,16 Although POP-Q is validated for examining women in all three positions, these studies were performed in older, non-pregnant women. [26][27][28][29] The studies comparing dorsal lithotomy position with sitting upright found a higher degree of prolapse in the upright position, whereas we believe this to be opposite in the case of an enlarged uterus.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…[14][15][16][17][18] A study following nulliparous Chinese women found a peak prevalence of anatomic POP in the third trimester of 35-37%, followed by a significant decline in the first year postpartum, although less in women delivered vaginally compared with women delivered by caesarean. 18 In contrast, a study following British women for up to 5 years postpartum found that vaginal delivery was associated with a persistent worsening in mean POP-Q stage, from 0.61 in the second trimester to a peak of 1.23 at 14 weeks postpartum, then 0.97 at 1 year postpartum and 1.06 at 5 years postpartum.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnancy, childbirth, obesity and constipation, which may lead to the increase of abdominal pressure, are considered to be important risk factors for POP (1)(2)(3)(4); mechanics serve a vital role in the incidence of POP. Further studies suggest that the occurrence of POP may be associated with an imbalance of the oxidation-reduction equilibrium in vivo (5,6).…”
Section: Introductionmentioning
confidence: 99%